Konsepsi Islam Tentang Perputaran Harta Dalam Upaya Empati Terhadap Kemiskinan - Suaidi Suaidi (Reflection : Islamic Education Journal, 2025)
Islam is a religion that places its concentration on regulating the economic order, so that the economic cycle is not only focused on one group or dominated by certain people. Islam applies strict sanctions against the hoarding of the economy that is only accessible to certain groups who have power, while the weak can only be witnesses. The economic gap that has been felt lately is a trigger for the compartmentalization of human life. Relationships between humans become foreign, do not know each other, let alone care about the problems felt by each individual. Life that feels foreign in the midst of society because of individualistic lifestyles is a trigger for crime and other bad behavior caused by economic inequality. Sayyidina Ali said that disbelief occurs due to persistent poverty. Even the crime of theft is also triggered by poverty.